Iatrogenic Nasolacrimal Duct Obstruction following Tooth Extraction in a Cat. (June 2013) - Paiva, Sávia Calline C. S.; Froes, Tilde R.; Lange, Rogério Ribas; Machado, Marcello; Pachaly, José Ricardo; Montiani-Ferreira, Fabiano
A 10-year-old DSH cat was referred for a dental evaluation and extraction procedure. Subsequently, the animal developed an acute onset of ocular discharge. Ophthalmologic examination revealed presence of unilateral ocular mucoid discharge leading to a diagnosis of epiphora secondary to nasolacrimal duct obstruction. Dacryocystorhinography was performed and confirmed the presence of a nasolacrimal duct obstruction, presumably acquired after an invasive dental procedure. Additionally, a vinyl cast in situ study of the nasolacrymal apparatus was performed to demonstrate the route of the nasolacrimal duct in the cat and its relationship to oral dental structures. This report documents an unusual case in which excessive inflammation/edema following tooth extraction caused acute epiphora secondary to extraluminal compression of the distal nasolacrimal duct.